Capillary barrier for slope stabilization - Rahardjo, Harianto (2008)
This report is a summary of the findings of RG 7/99 research project entitled "Capillary Barrier for Slope Stabilization".This project was undertaken with an objective to study the effectiveness of capillary barrier in stabilizing residual soil slopes against rainfall-induced slope failures under the climatic conditions in Singapore. The project involves examination of the behavior of a capillary barrier by conducting laboratory experiments in a one-dimensional 'soil column' and a two-dimensional 'infiltration box' under different soil types, soil thickness and different rainfall conditions relevant to tropical climate. The use of local compacted residual soils as a capillary barrier for minimizing infiltration was also investigated. The project also included numerical studies in order to understand and to recommend optimum design of capillary barriers as a soil cover to minimize infiltration.